Hans Christoph Buch’s Sansibar Blues and the fascination of cross-cultural experience in contemporary German historical novels about colonialism - Göttsche, Dirk (Wiley, 2012)
This article maps four different types of cross-cultural experience in contemporary historical novels about colonial Africa (colonialist, exoticist, intercultural, and transcultural) before focusing on Buch’s Sansibar Blues (2008) as a case study in German postcolonial memory and the literary use of transcultural voices. Together with Ilja Trojanow’s Der Weltensammler (2006) Sansibar Blues marks a new departure in the history of writing cross-cultural experience and representing the Other, but unlike Trojanow Buch uses partially authentic non-European voices that draw on the autobiographies of two prominent nineteenth-century figures in the linked histories of Zanzibar and Germany, Emily Ruete alias Princess Sayyida Salme of Oman and Zanzibar and ivory dealer Tippu Tip alias Hamed bin Mohammed. The article concludes with a detailed analysis of Buch’s adaptation of these sources.